2013
DOI: 10.2224/sbp.2013.41.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of the Brief Symptom Inventory 18 Among Irish College Students Over Four Weeks

Abstract: Of the currently limited available data on the mental health of students in Ireland the most notable are provided in the College Lifestyle and Attitudinal National (CLAN) Survey (Hope, Dring, & Dring, 2005). Recently, Houghton et al. (2012) found among students at an Irish university that women reported significantly higher levels of symptomatology than men on each of the three 6-item subscales of the Brief Symptom Inventory 18 (BSI 18; Derogatis, 2001) (anxiety, depression, and somatization) and the Global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…First, results indicated that rates of psychopathology remained stable over the follow-up period. This finding is consistent with research on the short-term temporal stability of the BSI subscales among healthy adults, which found no changes in subscale scores over time (Houghton et al, 2013). However, the lack of change in psychological symptoms is somewhat surprising, given that the participants were engaged in substance use treatment over the course of the assessment period, and drug treatment programs often alleviate secondary psychological distress (see e.g., Moos, Moos, & Andrassy, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…First, results indicated that rates of psychopathology remained stable over the follow-up period. This finding is consistent with research on the short-term temporal stability of the BSI subscales among healthy adults, which found no changes in subscale scores over time (Houghton et al, 2013). However, the lack of change in psychological symptoms is somewhat surprising, given that the participants were engaged in substance use treatment over the course of the assessment period, and drug treatment programs often alleviate secondary psychological distress (see e.g., Moos, Moos, & Andrassy, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Num estudo com estudantes alemães, no qual se aplicou o mesmo intervalo temporal, os valores destas correlações oscilaram entre .52 e .77 (Spitzer et al, 2011). Noutra amostra de estudantes, de nacionalidade irlandesa, as correlações oscilaram entre .44 e .59, tendo decorrido um mês entre as duas avaliações (Houghton et al, 2012(Houghton et al, , 2013. O maior intervalo temporal que identificámos entre as avaliações foi o do estudo de Meachen et al (2008), no qual doentes com traumatismo cranioencefálico responderam ao questionário novamente, entre 6 meses a 2 anos após a primeira avaliação, com as correlações a variar entre .57 e .67.…”
Section: Fidelidade Do Bsi 18unclassified
“…To this end, focus was on selected scale scores on the BSI: hostility, depression, anxiety, paranoia and psychoticism. Although there may have been some fluctuation in state over the 6 months of interest, scores have been shown to be generally stable at least over 4 weeks among young people, albeit university students (Houghton et al, 2013). Not all types of psychological state predicted all outcomes.…”
Section: Discussionmentioning
confidence: 99%